Agresi Provokasi dan Non-Provokasi pada Monyet Ekor Panjang (Macaca fascicularis, Raffles 1821) Terhadap Pengunjung di Kawasan Gunung Meru - Ainul Mardiah; Rizaldi Rizaldi; Wilson Novarino (Universitas Andalas, 2015)
The study on aggressive behavior of long-tailed macaques has been conducted from May to July 2016 at Gunung Meru, Padang, West Sumatra. This study aimed to compare between provocated and non-provocated aggressive behaviors of the macaques toward human visitors at Gunung Meru feeding site. This study used all-occurrence sampling method to record aggressive interactions from the macaques along the visitors behavior. One or more visitors were followed for ten minutes at the monkey feeding ground for a total 78.5 hours. The aggressive behaviors of long-tailed macaques either provocated or non-provocated were considerably high intensity level, including body contact and biting. Feeding contexts (i.e. food exposure, feeding, and contact feeding) become the main situation resulting provocative aggressions. This study suggest that monkeys and human visitors have a potential close contact and could be pathogen transmission.